NUTRITION IN TEENAGE PREGNANCY - Pertiwi, Nur Fitri Ayu; abida, liza laela; Nulaili, Helmi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Nutrition is an important component that must be met throughout the life cycle, especially for women. Women have nutritional needs according to their stage of development. Pregnant women have higher nutritional needs than women in general. The development of increasingly free associations has led to the emergence of pregnant women at a young age. Teenagers themselves still really need complete nutrition for their body development. Teenagers who have experienced pregnancy need special attention because their nutritional needs are not only related to their status as teenagers, but also need to pay attention to the condition of their bodies while pregnant. This study used a qualitative method with a phenomenological design. Informants were selected by purposive sampling. Data collection used in-depth interview techniques. Based on the results of the study, the fulfillment of balanced nutrition by informants was carried out according to health standards. Informants can also overcome difficulties faced such as nausea and vomiting, so that nutritional fulfillment can continue to be carried out. However, informants still lack knowledge about monitoring body weight during pregnancy as one of the indicators in fulfilling balanced nutrition for pregnant women. It is hoped that there will be a mentoring program for teenagers who experience unwanted pregnancies, especially mentoring during the pregnancy process and fulfilling their nutrition. Keywords: nutrition, teenager, pregnancy